2009
DOI: 10.1590/s1516-05722009000200011
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicação in vitro e aclimatação de Vernonia condensata Baker

Abstract: RESUMO:A espécie medicinal Vernonia condensata, vulgarmente conhecida por alumã, pertencente à família Asteraceae, possui propriedades analgésicas e de proteção gástrica. A crescente utilização dessa planta no Nordeste, pelas propriedades terapêuticas, justifica a necessidade de medidas que minimizem o impacto de sua exploração nas reservas naturais. O objetivo desse trabalho foi multiplicar in vitro plantas de alumã sob diferentes concentrações de BAP e aclimatá-las. Gemas axilares foram desinfestadas em solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 11 publications
2
11
0
8
Order By: Relevance
“…According to Shukla and Sawhney (1991), the presence of both BAP and ANA stimulates shoot production in several types of Brassica explants, but the response depends on the concentration used. Vicente et al (2009) also reported that high BAP concentrations reduced the NSE, most likely due to the phytotoxic effect of the cytokinin, which is consistent with the observed reduction in NSE at 120 days in the presence of 5 µM BAP.…”
Section: Resultssupporting
confidence: 82%
“…According to Shukla and Sawhney (1991), the presence of both BAP and ANA stimulates shoot production in several types of Brassica explants, but the response depends on the concentration used. Vicente et al (2009) also reported that high BAP concentrations reduced the NSE, most likely due to the phytotoxic effect of the cytokinin, which is consistent with the observed reduction in NSE at 120 days in the presence of 5 µM BAP.…”
Section: Resultssupporting
confidence: 82%
“…The surviving explants (shoots of nodal segments) were placed in 268-mL flasks containing 20 mL of MS culture medium supplemented with 1.0 mg L -1 of BAP (6-benzylaminopurine), according to VICENTE et al (2009), under the previously described growth room conditions, to increase the number of shoots over another 30 days.…”
Section: In Vitro Multiplicationmentioning
confidence: 99%
“…Almeida et al The National List of Medicinal Plants of Interest to the Public Health System (Relação Nacional de Plantas Medicinais de Interesse ao Sistema Único de Saúde -RENISUS) currently contains 71 species, including Vernonia condensata Baker (BRASIL, 2010). This plant is commonly known in Brazil as alumã (VICENTE et al, 2009) and boldo-da-bahia (AFONSO et al, 2015), among other names. It belongs to the family Asteraceae and has been used since colonial times to treat gastrointestinal problems and because of its analgesic properties (BOORHEM, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, este efeito nem sempre é conseguido, pois vários fatores podem interferir, tais como espécie em questão, o tipo de explante, dentre outros (ROGALSKI et al, 2003;DUTRA et al, 2004;MENDONÇA et al, 2004;BERTONI et al, 2006;RUBIN et al, 2007;RODRIGUES et al, 2009;VICENTE et al, 2009 MS 83,33a 95,83a 1,99a 2,96a 1,00a 1,17a 100,00a 100,00a 2,92b 3,33b 37,50a 29,17a 1,30a 1,74a BAP 65,27a 76,39b 1,57a 1,94a 1,03a 1,24a 98,61a 98,61a 4,51a 4,35a 16,67a 34,72a 1,09b 1,38b Cinetina 59,72a 72,22b 1,36a 2,18a 1,01a 1,09a 97,22a 100,00a 3,36b 3,47b 33,33a 22,22a 1,03b 1,35b Zeatina 72,22a 75,00b 1,80a 2,53a 1,08a 1,21a 91,94b 91,67a 2,32b 2,72b 38,89a 45,83a 1,34a 1,78a…”
Section: Resultsunclassified
“…No entanto, muitos experimentos conseguem com sucesso a aclimatação de plantas micropropagadas (GIRARDI et al, 2007;PORTELA et al, 2009;VICENTE et al, 2009). …”
Section: Etapas Básicas Da Micropropagaçãounclassified